E-008 Age-related differences in mechanical thrombectomy outcomes. (23rd July 2022) - Chandra, R; Kharal, A; Patterson, T; Moore, N; Hussain, S; Toth, G
Abstract : Introduction: Large vessel occlusion (LVO) is estimated to account for up to 39% of all ischemic strokes with around 50–60% of them resulting in post-ischemic stroke dependency and 96% of all post-ischemic stroke mortality. Advanced imaging modalities and efficient stroke systems of care have resulted in faster reperfusion times. There is limited data on the outcomes of thrombectomy as a function of age. We present a retrospective analysis on thrombectomy in younger (age 18–49 years) versus older (age >50 years) patients. Method: Retrospective single center analysis: Using the 'SlicerDicer' tool and our Cerebrovascular Stroke Database, we identified patients treated between 2017–2021, and performed an analysis of thrombectomy outcomes and predictors by age. Results: We have identified 48 patients between the age of 18–49 ('younger' group), and 436 over the age of 50 ('older' group). There were more males in the younger group (64.6% vs 48.1%; p=0.03) Younger versus older patients showed higher rates of favorable reperfusion (TICI2b-3) at 93.7% vs. 72.9% ( p = 0.0016) and better clinical outcomes (mRS 0–2) at 77.1% vs. 32.3% ( p <0.0001). The older group required more passes to achieve recanalization (4 or more passes: 4.3% vs 16.2%; p=0.035). Mortality rate was significantly less in the younger population (8.3% vs, 22.1%; p =0.026). We found that median groin puncture to reperfusion time was lower in younger population (32 vs. 69 mins; p =0.0044). The median groin puncture to first pass time was lower in younger population (32 vs 69 mins; p=0.056), but it failed to show statistical significance. Conclusion: Younger patients had better outcomes than their older counterparts after mechanical thrombectomy in our analysis. Other than younger age, higher rates of reperfusion, earlier recanalization, and less passes to recanalization were seen in association with better observed outcomes. A larger analysis is planned to identify further predictors of outcome in different age groups. Disclosures: R. Chandra: None. A. Kharal: None. T. Patterson: None. N. Moore: None. S. Hussain: None. G. Toth: None.